2015
DOI: 10.1111/nyas.12936
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and brain asymmetries in primates: a preliminary evaluation of two evolutionary hypotheses

Abstract: Contrary to many historical views, recent evidence suggest that species-level behavioral and brain asymmetries are evident in nonhuman species. Here, we briefly present evidence of behavioral, perceptual, cognitive, functional, and neuroanatomical asymmetries in nonhuman primates. In addition, we describe two historical accounts of the evolutionary origins of hemispheric specialization and present data from nonhuman primates that address these specific theories. Specifically, we first discuss the evidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 175 publications
1
46
1
Order By: Relevance
“…As far as some structural asymmetries go, there is support for this hypothesis within the primate line of evolution [64], but, as we have outlined, no such support comes from evidence of behavioural lateralization across a broad range of species. To put it simply, the small brains of insects are just as functionally lateralized as the large brains of vertebrates, even those of the apes.…”
Section: Why Lateralize Rather Than Grow Larger?mentioning
confidence: 88%
See 2 more Smart Citations
“…As far as some structural asymmetries go, there is support for this hypothesis within the primate line of evolution [64], but, as we have outlined, no such support comes from evidence of behavioural lateralization across a broad range of species. To put it simply, the small brains of insects are just as functionally lateralized as the large brains of vertebrates, even those of the apes.…”
Section: Why Lateralize Rather Than Grow Larger?mentioning
confidence: 88%
“…This strong bias could, of course, be coincidental, but it could be worth exploring further. In vertebrates, the population bias tends to be around 70%, although in sulphur crested cockatoos, the preference to hold food items in the left foot is above 90% and, hence, is equivalent to right handedness in humans (for a comparison of asymmetries in the use of limbs in human and non-human species, see Versace and Vallortigara [63] and Hopkins et al [64]). …”
Section: Disadvantages In Having An Asymmetrical Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct evaluations of the heritability of brain asymmetry in humans are not common in the literature [49], which may reflect a publication bias resulting from negative results. In chimpanzees, however, it has been reported that the AQ of grey matter volume shows low but significant heritability in the posterior region of the superior temporal gyrus, but not in the inferior frontal gyrus [49]. Because our previous studies have demonstrated that FA is preferentially located in the inferior frontal region in chimpanzees [12], we hypothesize that significant heritability for DA may be harder to identify in brain regions with strong FA.…”
Section: (A) Directional Asymmetry and Functional Lateralizationmentioning
confidence: 99%
“…We measured the IFG using methods that have been described in detail elsewhere [50]. At the start, the image was first oriented into the sagittal plane, where the most lateral slice with a fully visible fronto-orbital (FO) sulcus was identified.…”
Section: Methodsmentioning
confidence: 99%